Perceptions of Industrial Waste Management in Coastal Communities - Nahruddin, Zulfan; Firdaus, Ahmad (Generasi Sains Indonesia, 2024)
This study examines how economic development and its social impacts are perceived across different socio-economic groups in Palu, Central Sulawesi, a post-disaster urban context. It aims to assess whether economic growth promotes inclusive development or reinforces inequality. A quantitative cross-sectional survey was conducted with 150 respondents selected through stratified random sampling. Data were collected using structured questionnaires with a five-point Likert scale and analyzed using descriptive statistics, ANOVA, correlation, and regression techniques to evaluate relationships between socio-economic status and development perceptions. The findings show that economic development is generally perceived positively, particularly in infrastructure and employment. However, significant disparities exist across income groups, with higher-income respondents reporting more favorable perceptions. The results also indicate moderate levels of perceived inequality and declining social cohesion, especially among lower-income groups. Regression analysis confirms that income and education significantly influence perceptions, while economic development is negatively associated with social cohesion. Economic development supports recovery but may exacerbate inequality without inclusive policies and social integration strategies.